2018
DOI: 10.2460/ajvr.79.9.921
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the peripherally acting α2-adrenoceptor antagonist MK-467 on cardiopulmonary function in sheep sedated by intramuscular administration of medetomidine and ketamine and reversed by intramuscular administration of atipamezole

Abstract: OBJECTIVE To evaluate effects of the peripherally acting α-adrenoceptor antagonist MK-467 on cardiopulmonary function in sheep sedated with medetomidine and ketamine. ANIMALS 9 healthy adult female sheep. PROCEDURES Each animal received an IM injection of a combination of medetomidine (30 μg/kg) and ketamine (1 mg/kg; Med-Ket) alone and Med-Ket and 3 doses of MK-467 (150, 300, and 600 μg/kg) in a randomized blinded 4-way crossover study. Atipamezole (150 μg/kg, IM) was administered 60 minutes later to reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…18 It has been demonstrated in many species sedated with (dex)medetomidine that the duration of cardiovascular effects of VTX can be dose-dependent. 9,13,17,25,27 Therefore, the short effect of VTX on HR might be attributed to the low VTX dose, or the dose ratio between the alpha-2-adrenergic agonist and antagonist in the current study. 25,28 However, comparable doses in horses (0.15 mg kg −1 IV), administered 10 min after detomidine (0.02 mg/kg IV), led to an increase in HR that was sustained for 90 min after VTX administration.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…18 It has been demonstrated in many species sedated with (dex)medetomidine that the duration of cardiovascular effects of VTX can be dose-dependent. 9,13,17,25,27 Therefore, the short effect of VTX on HR might be attributed to the low VTX dose, or the dose ratio between the alpha-2-adrenergic agonist and antagonist in the current study. 25,28 However, comparable doses in horses (0.15 mg kg −1 IV), administered 10 min after detomidine (0.02 mg/kg IV), led to an increase in HR that was sustained for 90 min after VTX administration.…”
Section: Discussionmentioning
confidence: 79%
“…39 Studies in sheep and dogs showed lower haemoglobin concentrations when the alpha-2-adrenergic agonist was combined with VTX. 12,13,41 All animals showed a sufficient level plane of anaesthesia, and no difference was detected between treatments. However, the additional anaesthetic effects of tiletamine and zolazepam used in the study does not allow interpretation of the impact of VTX on the level or duration of the medetomidine-induced sedation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This concept has been well‐documented in various species (Honkavaara et al, 2011; Restitutti et al, 2012; Rolfe et al, 2012; Sainmaa et al, 2019; Siao et al, 2017; de Vires et al, 2016), including sheep (Adam, Huuskonen, et al, 2018; Adam, Raekallio, Keskitalo, et al, 2018; Adam, Raekallio, Salla, et al, 2018; Bryant et al, 1998; Raekallio et al, 2010). Moreover, vatinoxan has no appreciable impact on agonist‐induced sedation in many species (Adam, Raekallio, Keskitalo, et al, 2018; Adam, Raekallio, Salla, et al, 2018; Honkavaara Pypendop et al, 2017; Honkavaara et al, 2008, 2017; Raekallio et al, 2010; Restitutti et al, 2011; Siao et al, 2017; Tapio et al, 2018; Vainionpää et al, 2013; de Vries et al, 2016), nor has it shown antinociceptive effects when the agonist concentration is similar in plasma (Huuskonen et al, 2020). Recently, we demonstrated in sheep that premedication with vatinoxan alleviated dexmedetomidine‐induced bronchoconstriction and hypoxaemia, and prevented the opacity detected by computer tomography (CT) in the ventrolateral parts of lungs (Adam, Huuskonen, et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…According to the results of many studies, it was found that a decrease in cardiac output is not associated with a direct effect of α2-AM on myocardial contractility. It is secondary to an increase of total peripheral vascular resistance and a decrease in heart rate (HR) [25].…”
Section: Effects On the Cardiovascular Systemmentioning
confidence: 99%